2019
DOI: 10.1007/s42452-019-0863-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly porous, honeycomb like Ag–ZnO nanomaterials for enhanced photocatalytic and photoluminescence studies: green synthesis using Azadirachta indica gum

Abstract: The preparation of zinc oxide and silver doped zinc oxide nanoparticles using zinc nitrates and silver nitrates as oxidizers and Azadirachta indica gum as a fuel via solution combustion method at 500 °C. The synthesized nanoparticles were characterized by XRD, FTIR, UV-DRS, SEM and TEM studies; these materials were tested for photoluminescence and photocatalytic activity studies. The PXRD data indicated that the synthesized nanoparticles confirmed as hexagonal phase with average crystallite size of 13.33 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 45 publications
(40 reference statements)
1
31
0
Order By: Relevance
“…Photocatalytic properties of Ag-ZnO nanocomposites with various concentration of Ag in ZnO were studied by decomposition of MB. To study the photodegradation of MB, the change of absorbance at 664 nm wavelength at different time interval was monitored 56 . Figure 8 a–d depicts the time-dependent absorption spectra of MB aqueous solutions under visible light irradiation with Ag–ZnO nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalytic properties of Ag-ZnO nanocomposites with various concentration of Ag in ZnO were studied by decomposition of MB. To study the photodegradation of MB, the change of absorbance at 664 nm wavelength at different time interval was monitored 56 . Figure 8 a–d depicts the time-dependent absorption spectra of MB aqueous solutions under visible light irradiation with Ag–ZnO nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…7b. Chikkahanumantharayappa et al [50] reported such type of morphology occurs due to nucleation, growth, and self-accumulation. Were Zn 2+ and OH − ions ionize first in solution after the hydrolysis process.…”
Section: Ftir Analysismentioning
confidence: 99%
“…In the domain of nanotechnology, oxide nanoparticles (NPs) have gained importance due to their unique chemical properties, reduced particle size, and high density of corner or edge surface sites [1,2]. In recent years, semiconductor metal oxides NPs (MONPs) play a significant role in material science, that is, the fabrication of novel microelectronic circuits, piezoelectric devices, gas sensors, coatings, fuel cells, transparent conductors, biomedical devices, and catalysts [3][4][5][6][7]. Further, MONPs are preferred as sorbents for wastewater treatment containing pigments or dyes over the conventional purification methods, such as flocculation, filtration, precipitation, incineration, bio-treatment, ozonation, chemical coagulation, chemical oxidation, and adsorption processes based on solid adsorbents [2,5,8].…”
Section: Introductionmentioning
confidence: 99%